2020
DOI: 10.1016/j.rmcr.2020.101226
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis and COVID-19: Care considerations

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has demanded large scale changes in patient care. People with cystic fibrosis have unique considerations, including underlying lung disease and routine aerosolizing therapies, but there is insufficient evidence to create comprehensive practice guidelines. We share a case of a patient with CF and COVID-19 as well as alterations to routine CF care at a large academic center. Key considerations include accessible COVID-19 screening, augmented infection control prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Of these 28 included studies, 22 were case reports (describing single patients with individual data), two were case series (describing 7–42 patients with aggregate data), and four were cohort studies (describing 4–40 patients with aggregate data). Countries of study publication included the United States (n = 7) [ 7 , 9 , 21 25 ], Italy (n = 7) [ 26 32 ], Japan (n = 2) [ 33 , 34 ], Iran (n = 2) [ 35 , 36 ], the United Kingdom (n = 2) [ 37 , 38 ], Spain (n = 2) [ 39 , 40 ], Bahrain (n = 1) [ 41 ], China (n = 1) [ 42 ], France (n = 1) [ 43 ], the Philippines (n = 1) [ 44 ], Korea (n = 1) [ 45 ], and Canada (n = 1) [ 46 ], with publication dates ranging from April 15, 2020 to June 16, 2021. Table 1 describes the characteristics of these included studies and available information on their respective patient demographics in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 28 included studies, 22 were case reports (describing single patients with individual data), two were case series (describing 7–42 patients with aggregate data), and four were cohort studies (describing 4–40 patients with aggregate data). Countries of study publication included the United States (n = 7) [ 7 , 9 , 21 25 ], Italy (n = 7) [ 26 32 ], Japan (n = 2) [ 33 , 34 ], Iran (n = 2) [ 35 , 36 ], the United Kingdom (n = 2) [ 37 , 38 ], Spain (n = 2) [ 39 , 40 ], Bahrain (n = 1) [ 41 ], China (n = 1) [ 42 ], France (n = 1) [ 43 ], the Philippines (n = 1) [ 44 ], Korea (n = 1) [ 45 ], and Canada (n = 1) [ 46 ], with publication dates ranging from April 15, 2020 to June 16, 2021. Table 1 describes the characteristics of these included studies and available information on their respective patient demographics in detail.…”
Section: Resultsmentioning
confidence: 99%
“… 8 At the initial stages of the pandemic, most specialists thought otherwise—that this category of patients would have worse prognosis. 3 However, the CF registries from eight European countries that described 40 CF patients with confirmed COVID-19 disease have not shown any unique risk factor for acquiring or rendering the illness more severe among this heterogeneous group. 9 Another study from Spain showed CF patients having lower mortality from COVID-19 compared to the general population.…”
Section: Discussionmentioning
confidence: 96%
“… 2 Little is known about the effects of COVID-19 disease in cystic fibrosis (CF) cases. 3 Although CF patients always had a higher risk of complications from respiratory viral infections, not much is known if this is also applicable to COVID-19 disease. 4 …”
Section: Introductionmentioning
confidence: 99%
“…This is because of their chronically deteriorating lung function and susceptibility to viral infections, as well as the underlying pathophysiology of their condition and pro-inflammatory and respiratory nature of SARS-CoV-2. [2][3][4][5][6] Thus, this cohort is advised to 'shield' by self-isolating.…”
Section: Introductionmentioning
confidence: 99%